2022
DOI: 10.21203/rs.3.rs-1731798/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Oxford Nanopore Technologies and Illumina MiSeq sequencing with mock communities and agricultural soil

Abstract: Illumina MiSeq is the current standard for characterizing microbial communities in soil. The Oxford Nanopore Technologies MinION sequencer is quickly gaining popularity because of the low initial cost and longer sequence reads. However, the accuracy of MinION, per base, is much lower than MiSeq (95% versus 99.9%). The effects of this difference in base-calling accuracy on taxonomic and diversity estimates remains unclear. We compared the output of short MiSeq to short and full-length MinION 16S rRNA amplicons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This discrepancy could be attributed to the reduction in the number of reads following the filtering of low-quality reads. In addition, it was suggested that Illumina may have higher accuracy than nanopore sequencing (Kerkhof 2021, Stevens, Creed et al 2022), while we demonstrated an accuracy of over 90% for sequence lengths shorter than 300 bp and approximately 80% for sequence lengths longer than 800 bp in nanopore sequencing by aligning the TEM genes generated by nanopore to those generated by Illumina. Overall, we suggest that both platforms can be used for AMR profiling in food samples, but nanopore sequencing may be a better option.…”
Section: Discussionmentioning
confidence: 71%
“…This discrepancy could be attributed to the reduction in the number of reads following the filtering of low-quality reads. In addition, it was suggested that Illumina may have higher accuracy than nanopore sequencing (Kerkhof 2021, Stevens, Creed et al 2022), while we demonstrated an accuracy of over 90% for sequence lengths shorter than 300 bp and approximately 80% for sequence lengths longer than 800 bp in nanopore sequencing by aligning the TEM genes generated by nanopore to those generated by Illumina. Overall, we suggest that both platforms can be used for AMR profiling in food samples, but nanopore sequencing may be a better option.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, if the user requires classifying each read individually, further calculations are required. Yet when an accurate microbial community profile from 16S rRNA sequences is desired, recent studies are also favoring ONT sequencing paired with Emu (Petrone et al., 2023; Stevens et al., 2023).…”
Section: Commentarymentioning
confidence: 99%
“…The introduction of third generation, or long-read, sequencing technologies has enhanced NGS capabilities by allowing the sequencing of longer DNA segments. This advancement has revolutionised 16S rRNA gene studies, allowing for full-length 16S gene sequencing (~ 1500 bp), thereby substantially improving phylogenetic resolution, often to the species level [23,[28][29][30][31][32][33]. The platforms provided by PacBio and Oxford Nanopore Technology (ONT) are at the forefront of long read sequencing.…”
Section: Introductionmentioning
confidence: 99%